(untitled) (Journal of Cancer Research Updates, 2021)
Background: Different genetic variants in the ATM gene have been reported to be associated with breast carcinoma (BC). Purpose of the study was to consider the multi-insights experiments and explorations through the molecular, cellular and structural aspects of ATM. Methods and Results: D1853N polymorphism was traced in a proband with BC. DNA extracted from blood and tumor tissue was PCR-amplified and cloned to allelic localization of characterized variants. Protein expression and In silico analysis based on three different profiles involved in cell cycle were also performed to confirm mutational events. Findings revealed the molecular based sequential events as an eight-hit evolutionary pattern (8- Hit E.P) including D1853N as the first predisposing hit (inherited), pre-differentiation stage hits including IVS 36-8 T>C as the 2nd hit, V1833M as the 3rd hit, L1888L as the 4th, and somatic variants including IVS 36-46 C>T, L1842L, H1864H, and S1872R were considered as the 5-8th hits. Low protein expression of ATM in the majority of cells was observed, but the expression of cyclin E, CDC25A, P53, and Ki-67 was more diverse. Conclusions: Observations were reflective of the sequential molecular and cellular events through the entire patient’s life from the pre-differentiation embryonic stage and all through the post-birth periods. Mentioned hits seem to be effective on expression and function of ATM which confirmed by the expression and in silico analysis.